Os professores do atendimento educacional especializado e dos anos finais do ensino fundamental na rede municipal de Nova Prata - RS : articulação entre os profissionais - Marchesini, Paula (My University, 2022)
School Inclusion is a theme that has been present in numerous discussions about education in recent decades. This theme, which started a great movement from the 1990s, gains more focus from the National Policy of Special Education in the Perspective of Inclusive Education (PNEEPEI) of 2008. The legislation guides the education systems regarding the organization of the Special Education modality in regular school. Based on the legal guidelines, each system, each education network, each school institution is organized according to the interpretation it makes of these guidelines, which may vary from one context to another. In this means, the research aimed to understand the relationship between the teachers of Specialized Educational Assistance (AEE) and those of ordinary education, and if this relationship characterizes an articulation between these professionals as a way of enabling the process of inclusion in the final years of Fundamental Education of students target audience of Special Education. This exploratory research with a qualitative approach adopted as data collection technique the semi-structured interview, which was carried out in the municipality of Nova Prata/RS, with three female AEE teachers and six female teachers from the final years of Elementary School in two urban municipal schools. For data analysis, the content analysis proposed by Bardin (2016) was adopted. The research brings a review of studies found and related to the investigated theme and a theoretical framework that addresses the historical and political contextualization of Special Education in Brazil; the Specialized Educational Service from the perspective of inclusive education and the Multifunctional Resource Room as support; the Resource Room and common education: articulation between professionals to enable inclusive processes at school. In the research findings, it was evidenced that the AEE is perceived as a support for the Special Education student and, also, for the teachers of the final years. There is a consensus among the teachers that they play an important role in relation to the Inclusive Perspective of Special Education students. The AEE teacher maintains an articulating role for people and professionals involved with the schooling process of the Special Education student, but there are complaints about the distance and isolation between professionals due to incompatibility in time/activity, lack of time for both professionals exchange information and articulate strategies, and the fact that the resource room is not in the school where the student studies in the regular education classes. The participants of the research perceived that the articulation between AEE teachers and ordinary education teachers brings benefits to the planning of pedagogical strategies and the development of the Special Education student, but they manifest the need for time to articulate more effective strategies, without having to use the furtive moments of the gaps of everyday life. It was evident, in the teachers' reports, a feeling of helplessness regarding the actions of higher management in the face of impediments found in the school reality, alerting to the need for legal guarantees with forecast and provision of the necessary resources so that the articulation between Special Education and final years of Elementary School can be more pronounced. [resumo fornecido pelo autor]
A Inclusão Escolar é uma temática que tem marcado presença em inúmeras discussões a respeito da educação nas últimas décadas. Esta temática, que inicia um grande movimento a partir da década de 1990, ganha mais enfoque a partir da Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva (PNEEPEI) de 2008. A legislação orienta os sistemas de ensino quanto à organização da modalidade Educação Especial na escola regular. A partir das orientações legais, cada sistema, cada rede de ensino, cada instituição escolar organiza-se de acordo com a interpretação que faz dessas orientações, podendo apresentar variações de um contexto para outro. Dessa forma, a pesquisa teve como objetivo compreender a relação entre os professores do Atendimento Educacional Especializado (AEE) e os do ensino comum, e se essa relação caracteriza uma articulação entre esses profissionais como forma de viabilizar o processo de inclusão nos anos finais do Ensino Fundamental dos estudantes da Educação Especial. Esta pesquisa exploratória de abordagem qualitativa adotou como técnica de coleta de dados a entrevista semiestruturada, que foi realizada no município de Nova Prata/RS, com três professoras de AEE e seis professoras dos anos finais do Ensino Fundamental de duas escolas urbanas municipais. Para a análise dos dados, foi adotada a análise de conteúdo proposta por Bardin (2016). A pesquisa traz uma revisão de estudos relacionados à temática investigada e um referencial teórico que aborda a contextualização histórica e política da Educação Especial no Brasil; o Atendimento Educacional Especializado na perspectiva da educação inclusiva e a Sala de Recursos Multifuncionais como suporte; a Sala de Recursos e o ensino comum: articulação entre os profissionais para viabilizar os processos inclusivos na escola. Nos achados, evidenciou-se que o AEE é percebido como um apoio ao aluno da Educação Especial e, também, para as professoras dos anos finais. É consenso entre as docentes a consciência de que exercem um papel importante em relação à Perspectiva Inclusiva dos alunos da Educação Especial. A professora do AEE mantém uma função articuladora de pessoas e profissionais envolvidos com o processo de escolarização do aluno da Educação Especial, mas há queixas quanto ao distanciamento e isolamento entre as profissionais por incompatibilidade na hora/atividade, falta de um tempo para os dois profissionais trocarem informações e articularem estratégias, e o fato de a sala de recursos não estar na escola onde o aluno estuda nas turmas do ensino comum. As participantes da pesquisa percebem que a articulação entre as professoras do AEE e do ensino comum traz benefícios para o planejamento de estratégias pedagógicas e o desenvolvimento do aluno da Educação Especial, mas manifestam a necessidade de um tempo para articular estratégias mais eficazes, sem ter que utilizar os momentos furtivos das brechas do cotidiano. Ficou evidente, nos relatos das professoras, uma sensação de desamparo no que se refere às ações de gestores superiores frente aos impedimentos encontrados na realidade escolar, alertando para a necessidade de garantias legais com previsão e provisão dos recursos necessários para que a articulação entre Educação Especial e anos finais do Ensino Fundamental aconteça de forma mais acentuada. [resumo fornecido pelo autor]
Keywords: Educação especial; Educação inclusiva; Ensino fundamental - Nova Prata (RS); Special education; Inclusive education; Elementary School - Nova Prata (Brazil)